Penerapan Aplikasi Pencatatan Keuangan Digital Berbasis Aplikasi Buku Kas Harian pada UMKM Super Bubur Bang Jay di Kota Bengkulu - Susena, Karona Cahya; Herlin, Herlin; Efendi, Bahman; Syahputra, Paldi Awan (Jurnal Dehasen Mengabdi, 2025)
Financial recording is often an obstacle for MSME players, including Super Bubur Bang Jay in Bengkulu City. This community service activity aims to increase the financial management capacity of these MSMEs through the application of technology based on the Daily Cash Book application. The methods used include preparation, training, and evaluation of digital business financial records. The results of the activity show that the application of the Daily Cash Book is able to improve efficiency, accuracy, and transparency in financial recording. With this technology-based solution, Super Bubur Bang Jay MSMEs are better able to manage cash flow, prepare simple financial reports, and make more informed business decisions. The success of this program is expected to be a model that can be replicated in other MSMEs in Bengkulu City to support sustainable business development. Therefore, we, the Community Service Team, provide training in technology-based financial recording, especially for recording income and expenses which will result in good and neat bookkeeping. The method used is lectures in the form of interviews to partner managers of Super Bubur Bang Jay MSMEs. The results of the service are very helpful for managing partners ofSuper Bubur Bang Jay MSMEs in recording financial books.